2018
DOI: 10.15292/acta.hydro.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological modelling of the karst Ljubljanica River catchment using lumped conceptual model

Abstract: Modelling rainfall runoff is important for several human activities. For example, rainfall runoff models are needed for water resource planning and water system design. In this regard, the daily runoff was modelled using the Genie Rural, a 4-parameter Journalier (GR4J), Genie Rural, a 6-parameter Journalier (GR6J), and the CemaNeige GR6J lumped conceptual models that were developed by the IRSTEA Hydrology Group. The main difference among the tested models is in the complexity and processes that are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…), the mean annual rainfall sums exceed 2000 and 3000 mm, respectively, and due to the high elevation, snowfall and snowmelt are important processes. Moreover, a comparison of the GR6J and CemaNeigeGR6J models for the Ljubljanica River catchment revealed that not much difference in the models' performances could be detected [41]. Thus, one could argue that similar results would be obtained using the GR6J model version.…”
Section: Hydrological Modelmentioning
confidence: 91%
“…), the mean annual rainfall sums exceed 2000 and 3000 mm, respectively, and due to the high elevation, snowfall and snowmelt are important processes. Moreover, a comparison of the GR6J and CemaNeigeGR6J models for the Ljubljanica River catchment revealed that not much difference in the models' performances could be detected [41]. Thus, one could argue that similar results would be obtained using the GR6J model version.…”
Section: Hydrological Modelmentioning
confidence: 91%
“…In the scope of this study, we have decided to use the GR4J and GR6J models. These two models were selected because they have yielded good performance in previous applications to the catchments in Slovenia [10,11]. On the other hand, Slovenian Environment Agency, which is responsible for the flood forecasting uses the DHI NAM model [19].…”
Section: Hydrological Modelsmentioning
confidence: 99%
“…Nash-Sutcliffe efficiency (NSE), Kling-Gupta efficiency (KGE), and root mean square error (RMSE) criteria were applied in order to evaluate model performance [24,25]. The GR4J and GR6J models were already applied to some of the catchments located in Slovenia (see [10,11,26]).…”
Section: Hydrological Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we applied the lumped conceptual hydrological model named Génie Rural à 6 paramètres Journalier (GR6J) with snow module CemaNeige (e.g., [14][15][16][17][18]). The CemaNeige GR6J model version is implemented in airGR package [19,20] of R software [21], which was applied in this study.…”
Section: Hydrological Modelmentioning
confidence: 99%